Deixis in Rishi Sunak’s Speech, BBC News, and Ellen Interview: A Pragmatic Analysis - Pratama, Wijasena Aji (Jurnal Indonesia Sosial Sains, 2025)
Deixis represents a fundamental linguistic phenomenon that anchors language to context, requiring systematic investigation across different discourse genres to understand how speakers strategically employ deictic expressions to achieve communicative goals. Contemporary discourse analysis increasingly recognizes the critical role of deictic elements in shaping meaning, audience engagement, and contextual interpretation across political, journalistic, and entertainment communication. This study looks at how deictic expressions are employed in three different genres of speech: Rishi Sunak's political speech, a BBC news story about Louisiana's Ten Commandments law, and an interview with Bill Gates on The Ellen Show. The research aims to identify patterns of deictic usage across these distinct communicative contexts, analyze the functional distribution of five categories of deixis (personal, social, temporal, spatial, and discoursal), and evaluate how genre-specific requirements influence deictic strategies. The methodology employs qualitative comparative discourse analysis with quantitative frequency measurements to provide both depth and breadth of analysis across the selected texts. The results suggest that personal deixis is used the most, notably in speaking and interviews where the speaker and listener can talk to each other directly. Social and temporal deixis are also very essential since they show who is doing what, when, and how. The research implications demonstrate that deictic analysis provides valuable insights for understanding genre-specific communication strategies, enhancing cross-cultural communication competence, and informing pedagogical approaches to discourse analysis and pragmatics instruction. The study found that deixis is vital for structuring speech, making it clearer, and tailoring communication to diverse audiences and goals.